2012
DOI: 10.5958/j.0976-4763.3.2.007
|View full text |Cite
|
Sign up to set email alerts
|

A Review of National Biofuel Policy in India: A Critique- Need for Promotion of Alternative Feedstocks

Abstract: The last one to two decades have seen several countries stipulating a mandatory requirement of 5-10% blending of biofuels with petrol and diesel. The mandatory blending has triggered a rapid growth in the biofuel sector. Several governments have put in place biofuel policies that have a bearing right from the production of biofuels crops at the farm to their conversion into transport-grade biofuels to be utilised for blending purpose. This paper highlights the salient features of India's biofuel policy and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
13
0
Order By: Relevance
“…The economic and financial viability analysis has shown that feasibility of ethanol production from sweet sorghum stalk depends on the ethanol and feedstock pricing in addition to the recovery rate of ethanol. As an illustration, with a marginal improvement in recovery to 4.9% from the current level of 4.5%, and feedstock price fixed in 2012 was at US$20 t −1 of stalk, ethanol production became attractive at 50 cents L −1 when the administered price of ethanol in India was 48 cents L − (Basavaraj et al, 2012). The sweet-sorghum-to-ethanol scenarios, though positive, throws up mixed results.…”
Section: Economic Viability Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic and financial viability analysis has shown that feasibility of ethanol production from sweet sorghum stalk depends on the ethanol and feedstock pricing in addition to the recovery rate of ethanol. As an illustration, with a marginal improvement in recovery to 4.9% from the current level of 4.5%, and feedstock price fixed in 2012 was at US$20 t −1 of stalk, ethanol production became attractive at 50 cents L −1 when the administered price of ethanol in India was 48 cents L − (Basavaraj et al, 2012). The sweet-sorghum-to-ethanol scenarios, though positive, throws up mixed results.…”
Section: Economic Viability Assessmentsmentioning
confidence: 99%
“…The demand management of ethanol includes decisions to cap ethanol supply on considerations of fairness in distribution of ethanol to accommodate the needs of other sectors (potable and industrial). It was also recommended by the policymakers that the size of the ethanol blending program should be linked to the availability of feedstocks (Government of India, 2009;Basavaraj et al, 2012). Lower availability of molasses, and consequently higher prices in countries like India, has also affected the cost of ethanol production, putting ethanol blending programs at stake.…”
Section: Economic Assessment Economic Sustainability Of Biomass and Pmentioning
confidence: 99%
“…Energy is a critical input for economic growth and sustainable development in both developed and developing countries. The world's energy requirement for transportation is mostly fulfilled by non‐renewable fossil fuels such as coal, natural gas, and oil, which are expected to play a dominant role in energy scenario in future as well . The continuous rising demand of fossil fuels is expected to force nations to seriously consider using renewable, economical, and non‐polluting alternative sources of energy such as bioethanol, butanol, and biogas etc.…”
Section: Introductionmentioning
confidence: 99%
“…The world's energy requirement for transportation is mostly fulfilled by non-renewable fossil fuels such as coal, natural gas, and oil, which are expected to play a dominant role in energy scenario in future as well. 1,2 The continuous rising demand of fossil fuels is expected to force nations to seriously consider using renewable, economical, and non-polluting alternative sources of energy such as bioethanol, butanol, and biogas etc.. 3 Consequently, there have been increased R&D efforts w.r.t. bioconversion of agricultural waste biomass into biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the available resources for production of Biofuel is the need of the hour. Biofuels in the form of liquid fuels derived from plant materials, are entering the market, driven mainly by the need to reduce climate gas emissions, but also by factors such as oil price spikes and the need for increased energy security (Basavaraj et al, 2012). The challenge is to support biofuel development, including the development of new cellulosic technologies, with responsible policies and economic instruments to help ensure that biofuel commercialization is sustainable.…”
Section: Introductionmentioning
confidence: 99%